Strain Engineering in 2D Material‐Based Flexible Optoelectronics. Issue 1 (13th December 2020) - Du, Junli; Yu, Huihui; Liu, Baishan; Hong, Mengyu; Liao, Qingliang; Zhang, Zheng; Zhang, Yue
Abstract: Flexible optoelectronics, as promising components hold shape‐adaptive features and dynamic strain response under strain engineering for various intelligent applications. 2D materials with atomically thin layers are ideal for flexible optoelectronics because of their high flexibility and strain sensitivity. However, how the strain affects the performance of 2D materials‐based flexible optoelectronics is confused due to their hypersensitive features to external strain changes. It is necessary to establish an evaluation system to comprehend the influence of the external strain on the intrinsic properties of 2D materials and the photoresponse performance of their flexible optoelectronics. Here, a focused review of strain engineering in 2D materials‐based flexible optoelectronics is provided. The first attention is on the mechanical properties and the strain‐engineered electronic properties of 2D semiconductors. An evaluation system with relatively comprehensive parameters in functionality and service capability is summarized to develop 2D materials‐based flexible optoelectronics in practical application. Based on the parameters, some strategies to improve the functionality and service capability are proposed. Finally, combining with strain engineering in future intelligence devices, the challenges and future perspective developing 2D materials‐based flexible optoelectronics are expounded. Abstract : Although flexible optoelectronics based on 2D materials are successfully achieved in the past few years, how the strain affects the performance of 2D materials‐based flexible optoelectronics is confused. Here, a focused review on strain engineering in 2D materials‐based flexible optoelectronics to provide a perspective to develop the future application in flexible optoelectronic fields is provided.